Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing. (15th July 2023) - Tan, Weiwei; Long, Tao; Wan, Yanzhuo; Li, Bingchen; Xu, Zhilang; Zhao, Lei; Mu, Changdao; Ge, Liming; Li, Defu
Abstract: Diabetic chronic wound healing still faces huge clinical challenge. The arrangement and coordination of healing processes are disordered in diabetic wound caused by the persistent inflammatory response, microbial infection, impaired angiogenesis, resulting in the delayed and even non-healing wounds. Here, the dual-drug loaded nanocomposite polysaccharide-based self-healing hydrogels (OCM@P) with multifunctionality were developed to promote diabetic wound healing. Curcumin (Cur) loaded mesoporous polydopamine nanoparticles (MPDA@Cur NPs) and metformin (Met) were introduced into the polymer matrix formed by the dynamic imine bonds and electrostatic interactions between carboxymethyl chitosan and oxidized hyaluronic acid to fabricate OCM@P hydrogels. OCM@P hydrogels show homogeneous and interconnected porous microstructure, which possess good tissue adhesiveness, enhanced compression strength, great anti-fatigue behavior, excellent self-recovery capacity, low cytotoxicity, rapid hemostatic ability and robust broad-spectrum antibacterial activity. Interestingly, OCM@P hydrogels exhibit rapid release of Met and long-term sustained release of Cur, thereby to effectively scavenge extracellular and intracellular free radicals. Significantly, OCM@P hydrogels remarkably promote re-epithelization, granulation tissue formation, collagen deposition and arrangement, angiogenesis as well as wound contraction in diabetic wound healing. Overall, the multifunctional synergy of OCM@P hydrogels greatly contributes to accelerating diabetic wound healing, which demonstrate promising application as scaffolds in regenerative medicine. Graphical abstract: Unlabelled Image